MODEL PEMBELAJARAN ACTIVE LEARNING BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) DISABILITAS INTELEKTUAL DAN ATTENTION DEFICIT HYPERACTIVITY DI KELAS 3 SEKOLAH DASAR NEGERI KARANGWUNI KECAMATAN POLOKARTO KABUPATENSUKOHARJO - Dewi Sri Astuti; Para Mitta Purbosari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Active Learning modelbased on Small Group Discussion for children with special needs (ABK) withintellectual disabilities and Attention Deficit Hyperactivity Disorder (ADHD) in grade3 of SD Negeri Karangwuni, Polokarto District, Sukoharjo Regency. The studyused a qualitative descriptive approach with data collection techniques throughobservation, interviews, and documentation. The results of the study showed thatthe Active Learning learning model based on Small Group Discussion was able toencourage the activeness, understanding, and involvement of ABK students in thelearning process. Students with intellectual disabilities became more confident andactively asked questions, while students with ADHD showed high enthusiasm.Teachers play an important role as facilitators who adjust learning strategies tostudent characteristics. The obstacles faced include the teachers limitedunderstanding of students' special needs and the lack of supporting resources, butcan be overcome with small homogeneous groups and intensive mentoring.Overall, this model is effective in creating an inclusive and adaptive learningenvironment for the diversity of students in elementary schools.